Emergence of ferrimagnetism in Li-intercalated NiPS3. (26th October 2022) - Basnet, Rabindra; Ford, Dawn; TenBarge, Kaylee; Lochala, Joshua; Hu, Jin
Abstract: Intercalation has become a powerful approach to tune the intrinsic properties and introduce novel phenomena in layered materials. Intercalating van der Waals (vdW) magnetic materials is a promising route to engineer the low-dimensional magnetism. Recently, metal thiophosphates, M P X 3, has been widely studied because their magnetic orders are highly tunable and persist down to the two-dimensional limit. In this work, we used electrochemical technique to intercalate Li into NiPS3 single crystals and found the emergence of ferrimagnetism at low temperature in Li-intercalated NiPS3 . Such tuning of magnetic properties highlights the effectiveness of intercalation, providing a novel strategy to manipulate the magnetism in vdW magnets.